Impact of Western transmission of the Peking Gazette on Late-Qing China’s information security - Ling Chen; Lianjian Deng (Humanities & Social Sciences Communications, 2024)
Abstract The Peking Gazette, as a widespread and effective medium for the dissemination of important information from the Qing government, played a significant role in the internal governance of the empire. In the 19th century, Western missionaries, diplomats, and businessmen in China respected the authenticity and authority of the content in the Gazette, and carried out large-scale translations of political, social, cultural, economic, and military-diplomatic information into English. Western transmission of the Peking Gazette to some extent promoted cultural exchanges between China and the West and also provided the Western powers, which were in a period of expansion, with a wealth of political and military intelligence. The internally focused Qing dynasty was initially unaware of the Western transmission of the Peking Gazette and later took a series of doomed measures, leading to severe damage to national information security and political safety. The historical lessons of the Qing empire are enlightening for countries worldwide today: there is a need not only for openness and transparency but also for balancing the relationship between information disclosure and national security.